Outbreaks of bdelloid rotifers in and at adjacent wetland of a marine relict lake, Mago Ike on Soya Coast, East Antarctica: climate and limnological conditions - Kudoh, Sakae; Takahashi, Kunio; Wada, Tomotake (2022)
The 13th Symposium on Polar Science/Ordinary sessions [OB] Polar biology, Wed. 16 Nov. conference object